ANALISIS DAN IMPLEMENTASI MACHINE LEARNING DALAM MEMPREDIKSI KERUSAKAN LAPTOP MENGGUNAKAN METODE RANDOM FOREST (STUDI KASUS: BARAKA SERVICE DEPOK) - Tiara Ulfiah; Anis Mirza (Teknik Informatika Universitas Pamulang, 2025)
Laptops are essential electronic devices widely used in academic and professional activities; however, they are often prone to damage due to intensive usage. Manual damage identification by technicians is time-consuming and prone to human error. Thisresearch aims to develop a laptop damage prediction system based on machine learning using the Random Forest method. Thedataset was obtained from Baraka Service Depok, containing information such as year of purchase, daily crash frequency,overheat frequency, symptoms, and types of damage. The research process includes data preprocessing, model training, and webbased system implementation. The results show that the Random Forest model achieved an accuracy of 95% with stableperformance in recognizing various types of laptop damage. The developed system proved effective in assisting technicians byaccelerating the diagnostic process and improving work efficiency. Keywords: Machine Learning, Random Forest, Laptop Damage Prediction, Baraka Service Depok